2019
DOI: 10.1144/jgs2018-191
|View full text |Cite
|
Sign up to set email alerts
|

Biologically mediated weathering in modern cryptogamic ground covers and the early Paleozoic fossil record

Abstract: Specific micro-weathering features and biochemically-derived residues formed by living organisms can be used as biomarkers to infer the presence of biological communities within sedimentary units of ancient ecosystems. We examined basaltic soil minerals from modern cryptogamic ground covers (CGCs) in Iceland and compared these to two lower Palaeozoic fossil systems. Nine biologically-mediated weathering features (BWFs) were identified in modern soils including micron-scale surface trenching and penetrative tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…This difference might be a factor of time, where hole type 2 morphologies are created first and a longer duration of weathering leads to the creation of larger, more rounded and branched tunnels (hole type 1). Hole type 1 has rounded sides and circular cross section compared with type 2; these are reminiscent of 2D tunnel structure observed in other studies 18,25 which are reported as being from a biological origin, usually fungal 48 . Fungal tunnels within soil minerals have been explained as a result of dissolution and 'boring' by combined biomechanical forcing and biochemical alteration; the tunnel retains its shape following the death and degradation of the hyphae 24,44,45 .…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…This difference might be a factor of time, where hole type 2 morphologies are created first and a longer duration of weathering leads to the creation of larger, more rounded and branched tunnels (hole type 1). Hole type 1 has rounded sides and circular cross section compared with type 2; these are reminiscent of 2D tunnel structure observed in other studies 18,25 which are reported as being from a biological origin, usually fungal 48 . Fungal tunnels within soil minerals have been explained as a result of dissolution and 'boring' by combined biomechanical forcing and biochemical alteration; the tunnel retains its shape following the death and degradation of the hyphae 24,44,45 .…”
Section: Discussionsupporting
confidence: 56%
“…Our findings demonstrate that an assortment of markings are present on the surface of a soil grain of interest. These are reminiscent of the surficial bowls, tramlines, elongate troughs, and internal pore networks previously described as biologically mediated weathering features (BWFs) by 18 that are common in modern CGC soils. Although no microorganisms were observed colonising the grain surface from our XRM scans (the voxel size is not small enough to resolve them; Supplementary Methods S10), the presence of these features could suggest a biological origin.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Early development of terrestrial ecosystems often includes interactions between cryptogamic lithobiontic communities (cyanobacteria, green algae, lichens, and fungi together with other heterotrophic organisms), the lithomatrix of rocks and the given climatic conditions ( Mergelov et al., 2018 ; Mitchell et al., 2019 ). Since the occurrence of life on Earth, the interplay between the biotic and abiotic world is amongst the most ancient processes shaping the earth's surface.…”
Section: Introductionmentioning
confidence: 99%